2011
DOI: 10.1016/j.jnoncrysol.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Ni K-edge EXAFS in nanocrystalline nickel oxide using molecular dynamics simulations

Abstract: Analysis of atomic structure at the nanoscale is a challenging task, complicated by relaxation phenomena and thermal disorder. In this work, the x-ray absorption spectroscopy at the Ni K-edge was used to address this problem in nanocrystalline NiO (nanoNiO). The expansion of the average lattice but contraction of the Ni-O bonds in the first coordination shell were determined in nano-NiO at 300 K in comparison with bulk material. Accurate EXAFS analysis, based on a combination of classical molecular dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 56 publications
9
54
1
Order By: Relevance
“…For example, while it is about 8% theoretically as Moreau et al [38] calculated for 5.5 nm Ni nanoparticles, they actually found 41% reduction in both k-and r-space for this sample experimentally. Comparable experimental values of 25% in k-space and 20% in r-space for 6 nm NiO NPs were reported by Anspoks et al [36,37] While Cheng et al [34] reported 70% reduction in the first shell peak amplitude of FT-EXAFS spectra of Co nanoparticles, Haubold et. al.…”
Section: Exafs Studymentioning
confidence: 54%
See 1 more Smart Citation
“…For example, while it is about 8% theoretically as Moreau et al [38] calculated for 5.5 nm Ni nanoparticles, they actually found 41% reduction in both k-and r-space for this sample experimentally. Comparable experimental values of 25% in k-space and 20% in r-space for 6 nm NiO NPs were reported by Anspoks et al [36,37] While Cheng et al [34] reported 70% reduction in the first shell peak amplitude of FT-EXAFS spectra of Co nanoparticles, Haubold et. al.…”
Section: Exafs Studymentioning
confidence: 54%
“…This signature of long-range order is characteristic of a crystalline structure [35]. The considerably reduced amplitudes of spectral intensity of the Ni nanoparticles, compared to that of the bulk are usually attributed to nanosize effects [36][37][38]. Present 3.8 nm, 4.0 nm, 6.0 nm, 7.1 nm, 9.0 nm and 10.1 nm samples show reduction in EXAFS intensity of 61.7%, 62.6%, 61%, 34%, 24% and 20.5% in the k-space ( Figure 6) and 77%, 74%, 77% 62.6%, 51% and 43.6% in the r-space (Figure 7) compared to those of bulk nickel.…”
Section: Exafs Studymentioning
confidence: 99%
“…The developed force-field (FF) potential model allowed us to reproduce well within the multiple-scattering approach the Ni K-edge EXAFS spectrum of microcrystalline NiO, taking into account the contributions from the first six coordination shells (up to ∼5.5Å). 47,48 However, the same force-field model, applied to nanocrystalline NiO, predicted opposite direction of the relaxation for the first coordination shell of nickel compared to the results of conventional EXAFS data analysis based on the best fitting procedure.…”
mentioning
confidence: 84%
“…A more rigorous approach, based on the MD-EXAFS method, 16 has been used by us recently to study the structure relaxation and lattice dynamics in nanocrystalline (13 nm) NiO powder in comparison with microcrystalline oxide. 47,48 In our previous works 47,48 only the size reduction effect and related atomic structure relaxation have been considered when simulating nanocrystalline NiO. The developed force-field (FF) potential model allowed us to reproduce well within the multiple-scattering approach the Ni K-edge EXAFS spectrum of microcrystalline NiO, taking into account the contributions from the first six coordination shells (up to ∼5.5Å).…”
mentioning
confidence: 99%
“…Therefore, the use of a local structural probe such as X-ray absorption spectroscopy (XAS) renders very promising in the analysis of the NiO/oxide interface. Indeed, this scheme has been previously applied in the case of Ni x Mg l-x O solid solutions (Kuzmin et al, 1995), magnetron-sputtered nickel oxide thin films (Kuzmin et al, 1997;Anspoks & Kuzmin, 2011) and in crystallization studies of NiO nanoparticles (Meneses et al, 2007). XAS has proven to be an outstanding structural tool by allowing the determination of the local environment around a selected atomic species in a great variety of systems (Sayers & Bunker, 1988).…”
Section: Introductionmentioning
confidence: 99%